Familial pericentric inversion of chromosome 13 resulting in duplication 13q22→qter - Habedank, M (1982)
A 10-year-old male with a recombinant (13)dup q chromosome is reported. The recombinant chromosome originated from a maternal pericentric inversion which was present in two of his four normal sibs. A segregation analysis of 60 pregnancies from which one of the parents was a carrier of inv(13) showed a significant predominance of males among the viable offspring.